FEATURES OF THE CONSTRUCTION INDUSTRY IN THE CONTEXT OF ECONOMIC REFORMS CARRIED OUT IN UZBEKISTAN (World Economics and Finance Bulletin, 2023)
This article explores the features of the construction industry in the context of economic reforms carried out in Uzbekistan. The article analyzes the impact of reforms on the development of the industry, considers the opportunities and challenges faced by the construction sector. Based on current research and publications, the authors consider aspects such as infrastructure development, regulation, investment, human resources, sustainability and innovative technologies.
Keywords: Construction industry; economic reforms; Uzbekistan